Restoring mucosal barrier homeostasis by in situ formation of a living-synthetic therapeutic coating - Wei Yu; Huilong Luo; Bo Han; Sisi Lin; Qian Li; Rui Xue; Hui Tang; Xin Jia; Lu Wang; Jinyao Liu (Nature Communications)
Abstract The mucosal barrier consisting of physicochemical, immune, and microbial components is the first line of defense against external stimuli. Breakdown of the mucosal barrier causes the occurrences of various diseases, while methods capable of multifacetedly restoring mucosal barrier functions have been rarely reported. Here, we describe the restoration of the physicochemical, immune, and microbial homeostasis of the mucosal barrier by in situ formation of a living-synthetic therapeutic coating (LSTC). Through metal-phenolic complexation and π-π stacking interactions, ethyl gallate can chelate BiIII ions to form an adhesive coating on mucosal surfaces, which enables further hybridization with living bacteria. Due to the beneficial effects of BiIII and ethyl gallate and the probiotic characteristic of carried bacteria, LSTC increases the barrier integrity, mitigates mucosal inflammation, and maintains normal homoeostasis of the microbiota. In two murine models of aerobic vaginitis and vaginal candidiasis, LSTC demonstrates the potency to alleviate vaginal pathological injury and decrease vaginal inflammatory infiltration.